2006
DOI: 10.1089/ten.2006.12.2263
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Induce T Cell Anergy and Downregulate T Cell Allo-Responses via the TH2 Pathway: Relevance to Tissue Engineering Human Heart Valves

Abstract: To generate an ''off the shelf'' tissue-engineered heart valve, the cells would need to be of allogeneic origin. Here, we report the possibility of using human bone marrow-derived mesenchymal stem cells (MSCs) as a suitable allogeneic cell source for tissue-engineered heart valves. Proliferative responses of primary and primed CD4+ T cells to allogeneic MSCs were examined. A protein microarray system was used to detect soluble factors from supernatants collected from the T cell assays. MSCs are poor stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(99 citation statements)
references
References 41 publications
4
95
0
Order By: Relevance
“…As shown in Fig. 6B and C, PGE2 MSCs, although other reports showed that IFN-γ production decreased when T cells were cocultured with MSCs [16,17]. Moreover, NK cells were shown to produce IFN-γ when they interacted with allogeneic and autologus hBM-MSCs [20].…”
Section: Increased Expression Of Immunomodulatory Factors In Cad-mscsmentioning
confidence: 77%
See 1 more Smart Citation
“…As shown in Fig. 6B and C, PGE2 MSCs, although other reports showed that IFN-γ production decreased when T cells were cocultured with MSCs [16,17]. Moreover, NK cells were shown to produce IFN-γ when they interacted with allogeneic and autologus hBM-MSCs [20].…”
Section: Increased Expression Of Immunomodulatory Factors In Cad-mscsmentioning
confidence: 77%
“…MSCs can cause allogeneic immune cells to be suppressed through immunomodulatory factors that may be induced by interferon-γ (IFN-γ) secreted by activated T cells [30]. Moreover, it has been reported that MSCs can induce an increase in Th2 cells and regulatory T cells [16,17]; however, the exact mechanism of this immune modulation by MSCs is not well understood.…”
Section: Immuno Uorescence Stainingmentioning
confidence: 99%
“…MSC downregulated T cell responses through direct contact and secretion of anti-inflammatory and tolerogenic cytokines, which may involve the recruitment of regulatory T cells [31]. The general effects are to skew the immune response towards anti-inflammatory/tolerant phenotypes, including the shift from Th1 towards Th2, downregulation of IFN-g production from NK and reduction in the antibody productions of B cells [32].…”
Section: Properties Of Mscmentioning
confidence: 99%
“…Among these cells, bone marrowederived mesenchymal stem cells (BM-MSCs) possess immune privilege and immunosuppressive capacities [3] and can inhibit T-cell proliferation to allogeneic cellular and nonspecific mitogenic stimuli [4]. In addition, in vivo studies showed that infusion of allogeneic BM-MSCs have immunosuppressive activity [5] possibly through the preferential activation of CD4 þ CD25 þ Foxp3 þ regulatory T cells (T regs) [6].…”
mentioning
confidence: 99%